General Control of Information Systems - Devita Wahyu Azhari; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
In society and various fields of life, the advancement of information systems is very important. Controls must be installed to detect and resolve system disturbances in the information system. The purpose of this article is to learn about general information control systems. The methodology of this article is descriptive qualitative, and refers to secondary data from books, research findings published in journals, and topics related to the findings and discussion of this article. The focus of this article is on general controls in information systems, which are divided into several categories: documentation controls, hardware damage controls, organizational controls, physical security controls, and data security controls.